The dragon and the elephant: Agricultural and rural reforms in China and India - Gulati, Ashok; Fan, Shenggen (Johns Hopkins University Press, 2007)
China and India are the two most extraordinary economic success stories of the developing world. Both nations' economies have grown dramatically over the past few decades, elevating them from two of the world's poorest countries into projected economic superpowers. As a result, the numbers of Chinese and Indians living in poverty have rapidly fallen and per capita incomes in China and India have quadrupled and doubled, respectively. This book investigates the reasons for these staggering accomplishments and the lessons that can be applied both to other developing nations and to the problem of poverty that remains in these two countries. The contributors pay particular attention to agriculture and the rural economy, examining how initial conditions and investments and the prioritization and sequencing of different policies and strategies have led to successes, and how the agricultural and rural sectors connect to overall economic expansion. They also emphasize the importance of anti-poverty programs and safety nets in helping poor people escape poverty.